Quantifying and Mapping Atmospheric Potassium Deposition for Soil Ecosystem Services Assessment in the United States - Mikhailova, Elena A.; Post, Gregory C.; Cope, Michael P.; Post, Christopher J.; Schlautman, Mark A.; Zhang, Lisha (Frontiers in Environmental Science, 2019)
National Atmospheric Deposition Program (NADP) databases are important for quantifying and mapping the contribution of atmospheric deposition to soil provisioning ecosystem services. These databases provide information about the atmospheric deposition of potassium (K+) which is an essential element and component of many fertilizing materials. Atmospheric deposition flows (wet, dry, and total) serve as one input of K+ to soils; however, deposition varies spatially across the United States (U.S.). This study ranked an estimated provisioning value of soil ecosystem services due to atmospheric K+ deposition within the contiguous U.S. by state and region based on the 16-year period from 2000 to 2015. The total provisioning ecosystem value of atmospheric potassium deposition was over $406M (i.e., 406 million U.S. dollars) ($179M wet + $227M dry) per year based on a 5-year moving average of $500 per metric ton of potassium chloride (KCl) fertilizer in the U.S. The highest ranked regions for total value of K+ deposition per year were: 1) West ($86.5M), 2) South Central ($80.4M), and 3) Southeast ($80.2M). The highest ranked states for total value of K+ deposition per year were: 1) Texas ($44.3M), 2) California ($18.3M), and 3) New Mexico ($1.35M). Atmospheric potassium deposition is a source of K which is essential for human health. Given a U.S. population of 325.7 million people (2017), and a recommended daily intake of 4.7 g per person per day of K, it would require at least 1531 metric tons/day of potassium to ensure that every person is able to meet their daily potassium requirement. In terms of monetary value, it will cost nearly $1.5M per day based on a moving 5-year average U.S. price of $500 per metric ton of KCl fertilizer. The results of this study provide a methodology to estimate and map the value of atmospheric potassium deposition for ecosystem services assessments, which can be helpful in conducting nutrient audits at various scales to address the United Nations (UN) Sustainable Development Goals.